Genome-wide identification and expression profiling of EIL gene family in woody plant representative poplar (Populus trichocarpa) - ÖZYİĞİT, İBRAHİM İLKER (ELSEVIER SCIENCE INC, 2017)
This study aimed to improve current understanding on ethylene-insensitive 3-like (EIL) members, least explored in woody plants such as poplar (Populus trichocarpa Torr. & Grey). Herein, seven putative EIL members were identified in P. trichocarpa genome and were roughly annotated either as EIN3-like sequence associated with ethylene pathway or EIL3-like sequences related with sulfur (S)-pathway. Motif-distribution pattern of proteins also corroborated this annotation. They were distributed on six chromosomes (chrl, 3, 4 and 8-10), and were revealed to encode a protein of 509-662 residues with nuclear localization. The presence of ethylene insensitive 3 (EIN3; PF04873) domain (covering first 80 280 residues from N-terminus) was confirmed by Hidden Markov Model-based search. The first half of EIL proteins (similar to 80-280 residues including EIN3 domain) was substantially conserved. The second half (-300-600 residues) was considerably diverged. Additionally, first half of proteins harbored acidic, praline-rich and glutamine-rich sites, and supported the essentiality of these regions in the transcriptional-activation and protein-function. Moreover, identified six segmental and one-tandem duplications demonstrated the negative or purifying selective nature of mutations. Furthermore, expression profile analysis indicated the possibility of a crosstalk between EIN3-and EIL3-like genes, and co-expression networks implicated their interactions with very diverse panels of biological molecules. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Ethylene; Sulfur; Phytohormone; Poplar; SLIM1; Transcription factor; TRANSCRIPTION FACTORS; MOLECULAR CHARACTERIZATION; ETHYLENE RESPONSES; ARABIDOPSIS SLIM1; EIN3; SULFUR; CLONING; GROWTH; ETHYLENE-INSENSITIVE3; NITROGEN